Quissamã somos nós: pesquisa participante para construção de hipertexto sobre identidade cultural - Santo, Carmelita do Espírito (2003)
This participant research was developed in association with Quissamã community, located in Rio de Janeiro, represented by students, teachers and educational agents of six public schools. The objective of the research was to construct a digital hypertext, considered as a part of an information regime and significant structure [information] with the purpose of producing knowledge. We assume that is necessary to socialize information to produce knowledge, as part of the social role played by Information Science. The hipertext is considered as an instrument to produce, organize and to make information available in the Internet, known as a potential space to socialize information. The information contents of the hypertext reflects the information regime about the cultural identity of Quissamã, that has in its folklore one of the most expressive elements